Reading Darwin in Arabic, 1860-1950 - Elshakry, Marwa (The University of Chicago Press, 2016)
The gospel of science -- Evolution and the Eastern question -- Materialism and its critics -- Theologies of nature -- Darwin and the mufti -- Evolutionary socialism -- Darwin in translation